The Effectiveness of Robot Learning Media to Support Self-Directed Learning during the Covid-19 Pandemic - Ibnu Hartopo; Masduki Zakarijah; Akbar Aliyavi (Universitas Pendidikan Ganesha, 2023)
The impact of the COVID-19 pandemic on practicum learning is enormous. Restrictions on learning activities make it difficult for students to accept lessons. Learning models in distance learning must be adjusted for more optimal learning. The level of effectiveness of learning methods is a measure of the success of the learning process. This study aims to test the performance and effectiveness of smart robot learning media in supporting Self Directed Learning during the Covid-19 pandemic. The study used ADDIE development procedures and, for effectiveness tests using, pre-experimental research with a model one group pretest-post-test design. The respondents were 32 students majoring in industrial electronics engineering. The data analysis technique in this study uses quantitative description. The learning media used in this study is in the form of smart robot learning media that has been tested for the material's feasibility level and the media's feasibility. The effectiveness of robot learning media obtained a moderate category predicate with an increase in a score of 6.22 and an acquisition value of 0.55. The results of the effectiveness value show that robot learning media can support independent learning in the Robotic System Control subject.